Evaluation of E-learning at the Faculty of Engineering, Universitas Negeri Padang - Rizal, Fahmi; Wardina, Unung Vera; Ambiyar, Ambiyar (Universitas Negeri Padang, 2022)
Online learning can use an e-learning platform, e-learning content must be ideal and in accordance with the evaluation of the use of e-learning content. However, the gap that occurs is that e-learning content has never been started at Padang State University (UNP). The problems experienced by lecturers are not using content optimally, only using uploaded material, while content related to how to present material, learning methods in the use of e-learning and other content is not used. The purpose of this research is to make improvements to the implementation of e-learning in the UNP environment. The method used is a mixed method with quantitative and qualitative research, CIPP evaluation model, data collection using questionnaires. Based on the keywords from the CIPP evaluation results; 1) Context such as Principles, Goals, Environment, Needs. 2). Inputs such as e-learning delivery format, human resources (HR), User-friendly E-learning interface and service quality. 3) product category, namely Lecturer Competence. 4). Category of Lecturer Interaction Process, Teaching Method. The results of the survey obtained in Contexs have an average of 77.23, for input the average is 93.99, then the average process is 69.73, and the product is 68.25. So that it can provide recommendations for evaluating the implementation of e-learning by considering the process in the interaction section, on the product aspect of learning outcomes, on the input aspect the value is very good, then the component dimensions need to be improved.